KARAKTERISTIK PERKEMBANGAN BUNGA DAN BUAH 35 AKSESI ANGOLA KOLEKSI PUSAT PENELITIAN KELAPA SAWIT DI KEBUN ADOLINA PT PERKEBUNAN NUSANTARA IV - Sujadi Sujadi; Nanang Supena; Edy Suprianto (Pusat Penelitian Kelapa Sawit, 2019)
Information of oil palm flower and fruit development is very important in the observation plant morphology. This observation was carried out to complete information on vegetative and generative developments which are very useful for oil palm breeding. The success of plant breeding is measured from new varieties with specific advantages. This research used collections of Angola germplasm exploration which were planted in December 2012 at Adolina Estate of PT Perkebunan Nusantara IV. A total of 35 accessions were planted with RCBD designs in 2 trials. Vegetative observation per tree was carried out every year, since the plants were 2 years old. Observation of flower development is done by selecting 2 sample trees per accession by purposive sampling. A total of 70 trees were observed for flower development to become fruit every 10 days for each frond. Data on flower development were grouped by BBCH (Biologische Bundesantalt Bundessortenamt und Chemische Industrie) scale. In addition to the morphological and flower developmental stages, this study also calculated the age between developmental phases from the appearance of one leaf to the mature harvesting bunches in all midrib and tree samples. The results showed that generative development of the 35 Angolan accessions can be arranged according to the BBCH scale, beginning with the appearance of the first leaf, the appearance of the flower, female / male flowers blooming (receptic / anthesis), bunches formation to mature ripe bunches. AGO038 accession only requires 385 days (12.8 months), calculated from the time the first leaf appears to the mature ripe bunches, but AGO049 produces faster harvested ripe bunches when calculated from receptive female flowers of 144 days (4.8 months).